"Somebody’s watching me": surveying police surveillance of gangs - Valasik, Matthew A. (The Oxford handbook of gangs and society, 2024)
Tension remains between how gangs are policed by law enforcement and whether such practices are overtly invading the privacy of citizens or infringing their Fourth Amendment rights. Such concerns have risen in the era of big data and predictive analytics. This chapter discusses the policing of gangs, both conventionally and through data-driven approaches. As the implementation and use of data-driven policing across the 18,000 police jurisdictions in the United States remains inconsistent and uneven, the Los Angeles Police Department’s (LAPD) anti-gang policing strategies will be the focus given their longstanding engagement with street gangs and their employment of a variety of innovative approaches over the years. Overall, this chapter concludes that the policing of gangs remains a low-tech process focused primarily on reaction to and investigation of crimes.